Bamboo weaving inspired design of a carbonaceous electrode with exceptionally high volumetric capacity - Zhao, Zehua (2022)
A highly densified electrode material is desirable to achieve large volumetric capacity. However, pores acting as ion transport channels are critical for high utilization of active material. Achieving a balance between high volume density and pore utilization remains a challenge particularly for hollow materials. Herein, capillary force is employed to convert hollow fibers to a bamboo-weaving-like flexible electrode (BWFE), in which the shrinkage of hollow space results in high compactness of the electrode. The volume of the electrode can be decreased by 96% without sacrificing the gravimetric capacity. Importantly, the conductivity of BWFE after thermal treatment can reach up to 50,500 S/m which exceeds that for most other carbon materials. Detailed mechanical analysis reveals that, due to the strong interaction between nanoribbons, Young's modulus of the electrode increases by 105 times. After SnO2 active materials is impregnated, the BWFE/SnO2 electrode exhibits an exceptionally ultrahigh volumetric capacity of 2000 mAh/cm3.